Estimation of Atherogenic Index of Plasma, Prolactin, and Some Other Hormones in Polycystic Ovarian Syndrome in Lean Women - Hamad, Sara S.; Ahmed, Sardar N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder with an increase in androgen levels that influences young women during reproductive age, and it is associated with different reproductive health issues and has significant influences on metabolic pathways. This study focused on the estimation of the atherogenic index of plasma (AIP), LDL/ HDL ratio, Prolactin, and some other parameters that influenced lean women with PCOS. A total of 120 women from Shahid Doctor Khalid Hospital (Koya health centers) in Koya-Erbil Governorate, aged from 25 to 45 years, were distributed into 90 lean women patients with PCOS and 30 healthy individuals who have no PCOS as control groups. This work revealed that the parameters of serum Prolactin, LH, FSH, TSH, Testo, insulin, FBG and HOMA-IR were significantly elevated in lean women with PCOS groups as compared with normal groups. The lipid profile parameters of serum T-Chol, TG, LDL, and VLDL were significantly higher in the PCOS group when compared with healthy individuals, whereas the serum level of HDL was significantly decreased in the PCOS group compared to healthy persons. No significant difference was found for serum Mg among PCOS and control groups. This study indicates from the calculation of BMI (kg/m2) that women with PCOS have normal body weight. AIP is detected as a useful biomarker to indicate the cardiovascular disease (CVD) risk in the future. The results of this study indicate that those lean women with PCOS have insulin resistance (IR) due to the high levels of HOMA-IR.